Mediação e judiciário: problematizando fronteiras psi-jurídicas - Catão, Ana Lucia Prado (2009)
This study addresses Conflict Mediation as an institutionalising field, in close relation with judicial practices. Mediation is known as an alternative dispute resolution method, systematised in the US in the 1970 s. Along with Conciliation and Arbitration, it s becoming more widespread in Brazil, specially in the juridical field, being adopted as a political strategy in the reform of Judicial System. Mediation tends to be presented by mediators as a practice where one can find psychological and juridical knowledge and doings, but distinguished from both psychology and law fields. Considering this context, our research intended to identify and analyse Brazilian Mediation territory institutionalisation from two emphases: the relationship established between Mediation and Judiciary and the subjectivation process on judicial practices. That s what we have called psy-juridical borders. We have approached these themes through institutional analysis from a French perspective (René Lourau) and with some Michel Foucault theoretical supports. In chapter 1 we have scanned the field, showing the territory under construction and emphasising where Mediation and Judiciary reach each other. In chapter 2 we have focused articles written by psychologists and lawyers and their formulations about Mediation, showing its senses and effects on subject and society. In chapter 3 we have explored the experience of subjectivity produced in judicial Mediations − normalisation and ethical constitution of the subject were found. With Foucault perspective we were able to problematise the ethical-political choice which institutionalise such practices in Judiciary